Interaction between adipocytes and macrophages participates in chick subcutaneous adipose tissue angiogenesis under cold stress conditions - Yuelang Zhang; Jingxuan Li; Shanhe Wang; Mingli Wu; Haidong Zhao (Animal Biotechnology)
Previous studies have shown that subcutaneous adipose tissue is an important energy supply organ for chicks before and after birth, except yolk. So far, the significance of large deposits of subcutaneous adipose tissue in chicks is unclear. Therefore, this study takes the information interaction between adipocytes and macrophages as the starting point to explore whether adipocytes and macrophages could participate in adipose tissue fibrosis, angiogenesis, adaptive thermogenesis and other related functions in a specific metabolic environment. Under cold stress, the expression levels of genes related to lipidolysis, lipid transport and fatty acid oxidation in adipose tissue of chicks were significantly increased, but the expression levels of genes related to mitochondrial uncoupling were not significantly changed. Through Masson staining of adipose tissue of chicks under cold stress, it was found that the level of vascularization in adipose tissue of chicks was significantly increased. We found that the interaction between adipocyte and macrophage could participate in the angiogenesis related process of adipocytes in chicks through the HIF1A–VEGFA pathway. The analysis of lipid metabolism in subcutaneous adipose tissue of chicks from the perspective of cell heterogeneity will expand the understanding of lipid metabolism in chicks and provide a theoretical basis for chick rearing.